Development and Characterization of Thai Fish Cake (Tod Mun Pla) Fortified with Sago Palm Weevil Larvae (Rhynchophorus ferrugineus) - Kingwascharapong, Passakorn; Petsong, Kantiya; Karnjanapratum, Supatra; Pongsetkul*, Jaksuma (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Edible insects are promoted as new alternative sustainable sources of food. However, consumption is still limited to specific groups of consumers because of food neophobia and unwillingness to eat insects. One of the techniques that can alleviate the neophobia is to process edible insects into familiar foods. Thus, the aim of this study was to develop and characterize Thai fish cake (Tod mun pla, TFC) fortified with sago palm weevil larvae (Rhynchophorus ferrugineus) (SPWL). Different ratios of fish mince: sago palm weevil at 100:0, 80:20, 60:40, 40:60, 20: 80, (w/w), were investigated. The breaking force, deformation and gel strength of TFC increased (P<0.05) while the expressible moisture content (P<0.05) decreased when the ratio of SPWL was increased. Texture profile analysis (TPA) of TFC was improved when low levels of SPWL were added, particularly at the treatment of 80:20 (P<0.05). The color of TFC intensified when fortified with SPWL (P<0.05). Oily characteristics of TFC were observed with SPWL incorporation at a higher level as indicated by stereomicroscope, a result which was concomitant with the greater fat content (P<0.05). Fortifying the TFC with SPWL at the ratio of 80:20 (w/w) provided the highest sensory acceptance for all attributes amongst all treatments. However, higher ratios of SPWL had a negative effect on sensory acceptance. Therefore, TFC fortified with SPWL at an appropriate level could reduce food neophobia and increase sensory acceptance. Keywords: Thai fish cake; Tod mun pla; edible insects; sago palm weevil larvae *Corresponding author: Tel.: (+66) 0-4422-4371 E-mail: jaksuma@sut.ac.th